Work Stress: The Effect of Psychological Capital and Quality of Work Life of Sales Employees - Esterina, Meriam; Kusuma, Patria Jati; Saputra, Immanuel Jefri (Jurnal Sains dan Teknologi, 2023)
High work demands and intense competition among employees can be a source of work stress. Organizations need to pay attention to things that can affect the work stress of their employees, especially in the sales force which is the main key to product marketing. This study aims to determine the effect of psychological capital and quality of work life on work stress. Research conducted at PT. Cendana Giri Purworejo on sales force. The sampling technique used is the Non-Probability Sampling Technique with a total sample of 100 people. This research is a quantitative study, which uses three questionnaires, namely the psychological capital questionnaire, the quality of work life questionnaire, and the work stress questionnaire. The data obtained were then analyzed using SPSS 20 with multiple regression methods. The results of the study show that there is a positive significant influence between psychological capital and quality of work life on work stress.